Extracellular enzymes of Fusarium graminearum isolates - Gisele Eleonora Kikot; Roque Alberto Hours; Teresa María Alconada (Brazilian Archives of Biology and Technology, 2010)
Fusarium graminearum isolates from three different agroecological regions in Argentina were examined according to the production of different extracellular enzyme activities of potential biotechnological interest: pectinases (PGase: polygalacturonase and PMGase: polymethylgalacturonase), cellulase (CMCase: carboxymethylcellulase) and hemicellulase (xylanase). The isolates were grown in minimum salt medium supplemented with 0.25% glucose, 0.125% citric pectin and 0.125% oat bran as carbon sources and/or enzyme inducers. PGase activity was detected early (after two days of incubation) in all the cultures; it was found to be the highest for all the isolates. PMGase was high only for those isolates of the II region. CMCase and endoxylanase activities were particularly found at late stages (after four and seven days of incubation, respectively) and the maximum values were lower than pectinase activities.